1999
DOI: 10.1111/j.1348-0421.1999.tb02466.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of Endothelial Cell Line ECV304 Persistently Infected with Orientia tsutsugamushi

Abstract: Endothelial cells are major targets of Orientia tsutsugamushi. To examine the consequences of the infection of endothelial cells with O. tsutsugamushi, we used human endothelial cell line ECV304. Persistent infection was established and infected cultures could be maintained for over seven months without the addition of normal cells. The heavily infected cells became round and floated in the culture medium, harboring large numbers of organisms inside them. Some of the infected ECV304 cells showed features of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 31 publications
(25 reference statements)
0
25
0
Order By: Relevance
“…Apoptosis of the host cells would deprive the obligate intracellular pathogens of their intracellular hideouts, while apoptosis of infected macrophages or lymphocytes may seriously compromise the host defense mechanisms (22). Previous studies on the apoptosis of O. tsutsugamushi-infected cells (12,14) have shown that apoptosis is a relatively late event and predominantly involves cells that are heavily laden with intracellular bacteria. The mechanisms of delayed apoptosis induced by O. tsutsugamushi have been elucidated in this study.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Apoptosis of the host cells would deprive the obligate intracellular pathogens of their intracellular hideouts, while apoptosis of infected macrophages or lymphocytes may seriously compromise the host defense mechanisms (22). Previous studies on the apoptosis of O. tsutsugamushi-infected cells (12,14) have shown that apoptosis is a relatively late event and predominantly involves cells that are heavily laden with intracellular bacteria. The mechanisms of delayed apoptosis induced by O. tsutsugamushi have been elucidated in this study.…”
mentioning
confidence: 99%
“…It has been shown previously that O. tsutsugamushi can induce apoptosis in a variety of host cells, including lymphocytes and endothelial cells (11,12,14). Many intracellular bacteria have evolved mechanisms by which to down-regulate apoptosis of the cells they infect (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we found that the ECV304 cells that were heavily infected became round and floated in the culture medium, whereas other cells still adhered to the culture flask and had only a relatively small number of bacteria inside the cell (10). In this study, we found that there were more dead bacteria in the nonadherent cells than in the adherent cells, as judged by bacterial viability count of preparations from each of the cell groups.…”
Section: Only Live Bacteria Express M686-13 Antigenmentioning
confidence: 49%
“…tsutsugamushi. The Boryong serotype of O. tsutsugamushi (4) was cultivated in ECV304 cells as described previously (10). The cells, once infected, were cultivated until the heavily infected cells detached from the culture substrate.…”
Section: Methodsmentioning
confidence: 99%